INVESTIGATING PRE-SERVICE TEACHERS’ TPACK COMPETENCE IN ELT PRACTICUM SETTINGS: A MIXED-METHOD EXPLORATION - Adib Ahmada (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2026)
This study investigates the Technological Pedagogical Content Knowledge (TPACK) competence of pre-service teachers during their English Language Teaching (ELT) practicum using a mixed-method design. Five pre-service teachers participated in a one-month teaching practicum at MTs N 2 Banyuwangi. Quantitative data were collected through a 15-item TPACK self-assessment questionnaire, measuring four core domains: Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), and the integrative TPACK construct. Qualitative data were obtained from document analysis of lesson plans, instructional materials, teaching media, and reflective reports. The results show that participants demonstrated strong CK (Mean = 4.3) and solid PK (Mean = 4.05), while TK emerged as the weakest domain (Mean = 3.3). The integrative TPACK score (Mean = 3.55). These findings indicate clear differences across TPACK domains, with CK being the strongest and TK the weakest after the one-month practicum. The study contributes to understanding TPACK development in Indonesian ELT practicum settings and underscores the importance of institutional support for meaningful technology integration. Keywords: TPACK, pre-service teachers, mixed-method